2022
DOI: 10.3390/ijerph19041948
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Short-Term Alcohol Drinking in Patients with Alcohol Use Disorders during the Third Wave of the COVID-19 Pandemic: Prospective Study in Three Addiction Outpatient Centers in France

Abstract: The present study investigates the extent to which the COVID-19 crisis disturbed different life domains of patients with alcohol use disorder (AUD) and assessed the associations between these disturbances and the risk of short-term alcohol drinking. All patients aged >18 years receiving outpatient care at three addiction treatment facilities from 15 April to 30 May 2021 were eligible for inclusion in the study. A trained resident assessed the extent to which the COVID-19 crisis affected their professional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As in other studies, our logistic regression analysis results, confirmed the expected associations between the increase in craving during follow-up and earlier relapse ( 46 ). Craving has been identified as a mediating factor between psychological problems and increased alcohol use in AUD patients during the pandemic ( 20 ). The treatment of craving is essential for a comprehensive approach to addictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other studies, our logistic regression analysis results, confirmed the expected associations between the increase in craving during follow-up and earlier relapse ( 46 ). Craving has been identified as a mediating factor between psychological problems and increased alcohol use in AUD patients during the pandemic ( 20 ). The treatment of craving is essential for a comprehensive approach to addictions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study conducted on the general population, reported that during the first year of the pandemic alcohol consumption increased among subjects who reported more psychological distress ( 19 ). Adding on, craving has been identified as a mediator between psychological problems and increased alcohol use in patients with alcohol use disorder (AUD) during the pandemic ( 20 ). However, one study among AUD patients did not find an association between lockdown measures and alcohol consumption ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the findings of previous studies targeting patients with SUD, including AUD, have confirmed a high comorbidity of depression, anxiety, and suicide risk during the COVID‐19 pandemic (Blithikioti et al, 2021; de Moura et al, 2022). Loneliness and craving were associated with an increased risk of relapse among those patients (Bonny‐Noach & Gold, 2021; Constant et al, 2022). These findings suggest that the condition of people seeking recovery from AUD may have worsened during COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“…Communications by professionals as well as qualitative research has pointed to challenges in the treatment of SUD, particularly in regard to increased psychosocial stress and reduced access to treatment services ( 55 59 ). While some research has found an ambiguous development of consumption patterns in individuals with alcohol use disorder (AUD) ( 60 62 ) and SUD ( 63 ), a number of publications related an increased risk of relapse in patients with AUD ( 64 67 ) and an increase of addictive behavior in other SUD ( 68 , 69 ). This has been linked to increased psychosocial strain due to COVID-related stressors ( 62 , 64 , 67 69 ) with loneliness in particular having been identified as a factor associated with higher craving ( 68 ).…”
Section: Introductionmentioning
confidence: 99%
“…While some research has found an ambiguous development of consumption patterns in individuals with alcohol use disorder (AUD) ( 60 62 ) and SUD ( 63 ), a number of publications related an increased risk of relapse in patients with AUD ( 64 67 ) and an increase of addictive behavior in other SUD ( 68 , 69 ). This has been linked to increased psychosocial strain due to COVID-related stressors ( 62 , 64 , 67 69 ) with loneliness in particular having been identified as a factor associated with higher craving ( 68 ). To expand these findings, we undertook a longitudinal study on psychological distress and its relationship with loneliness and social support in individuals suffering from SUD in comparison to a community reference group without self-reported mental health disorders.…”
Section: Introductionmentioning
confidence: 99%